2019
DOI: 10.3324/haematol.2018.204123
|View full text |Cite
|
Sign up to set email alerts
|

NCOA4 maintains murine erythropoiesis via cell autonomous and non-autonomous mechanisms

Abstract: Ncoa4 mediates autophagic degradation of ferritin, the cytosolic iron storage complex, to maintain intracellular iron homeostasis. Recent evidence also supports a role for Ncoa4 in systemic iron homeostasis and erythropoiesis. However, the specific contribution and temporal importance of Ncoa4-mediated ferritinophagy in regulating systemic iron homeostasis and erythropoiesis is unclear. Here, we show that Ncoa4 has a critical role in basal systemic iron homeostasis and both cell autonomous and non-autonomous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
2
51
0
Order By: Relevance
“…An erythropoietic role for NCOA4 was suggested also in vivo in zebrafish embryos treated with morpholinos to Ncoa4 (4). A moderate-severe anemia was observed in Ncoa4-ko mice at birth, mostly rescued in adult animals (9,10). Despite all these findings suggest a role for NCOA4 in erythropoiesis, a formal proof that anemia of adult Ncoa4-ko mice is due to loss of protein activity in erythroid cells is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An erythropoietic role for NCOA4 was suggested also in vivo in zebrafish embryos treated with morpholinos to Ncoa4 (4). A moderate-severe anemia was observed in Ncoa4-ko mice at birth, mostly rescued in adult animals (9,10). Despite all these findings suggest a role for NCOA4 in erythropoiesis, a formal proof that anemia of adult Ncoa4-ko mice is due to loss of protein activity in erythroid cells is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these findings suggest a role for NCOA4 in erythropoiesis, a formal proof that anemia of adult Ncoa4-ko mice is due to loss of protein activity in erythroid cells is still lacking. Recent data (10) point toward both an autonomous and nonautonomous effect of NCOA4 in erythropoiesis. The Authors generated a conditional tamoxifen-induced total Ncoa4-ko model and a tissue specific one [through the expression of CRE-recombinase under the control of Erythropoietin Receptor (EPOR) promoter in Ncoa4-floxed transgenic animals].…”
Section: Introductionmentioning
confidence: 99%
“…To date, little is known about the expression of NCOA4 in the human brain, however, it’s expression in murine and rat brains has been identified ( Siriett et al, 2006 ; Kollara and Brown, 2010 ). Acute systemic consumption of NCOA4 shows accumulation of FTH1 within a week, which suggest a potential role of NCOA4 for FTH1 turnover in the brain ( Santana-Codina et al, 2019 ). Interestingly, excessive iron measured as serum ferritin was also associated with poor prognosis following ischemic stroke ( García-Yébenes et al, 2012 ), indicating the important role of ferritin as an iron carrier to mediate iron storage and release under ischemic conditions.…”
Section: Crosstalk Between Autophagy and Ferroptosismentioning
confidence: 99%
“…Previous reports have shown that whole body NCOA4 deficiency has variable effects on systemic iron parameters (6,8). To characterize and confirm the role of NCOA4 in systemic iron homeostasis, we have generated a NCOA4 knockout (KO) mouse line by using CRISPRmediated guide RNA ( Figure 3A-C).…”
Section: Systemic Ncoa4 Deficiency Causes Tissue Iron Sequestration Amentioning
confidence: 99%
“…Ferritinophagy occupies a critical place in systemic iron homeostasis and is itself regulated by cellular iron levels (6). More recent discoveries about the role of NCOA4 in erythropoiesis highlights its connection with mammalian oxygen carrying function (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%